Process for producing ammonium molybdate by ion exchange method
Through the application of ion exchange method and modified resin, the problem of separation difficulties in the ammonium molybdate production process is solved, the molybdenum resource recovery rate and product quality are improved, and cost reduction and impurity removal are achieved.
Patent Information
- Application Number
- CN202510308431.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-17
AI Technical Summary
There are problems such as separation difficulties in the existing ammonium molybdate production process, resulting in high production costs and low molybdenum metal recovery rate.
Molybdenum is converted to sodium molybdate through sodium calcination and water immersion processes, followed by adsorption and desorption using a modified anion exchange resin, and finally treated by a cation exchange resin and a precipitant to obtain pure ammonium molybdate.
It improves the recovery rate of molybdenum resources and the quality of ammonium molybdate products, reduces production costs, and realizes effective removal of impurities such as arsenic, silicon, and phosphorus.
Smart Images

Figure CN119822406A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of molybdenum metallurgy, and in particular relates to a process for producing ammonium molybdate by an ion exchange method. Background Art
[0002] Molybdenum is an important non-renewable strategic resource with high melting point and excellent ductility. It can be used in industrial catalysis, new energy, aerospace, electronic information, nuclear power and other industries. The distribution of molybdenum is very small, mainly in the form of molybdenum sulfide or molybdate symbiosis with other minerals. It must go through mining, ore enrichment, smelting, chemical purification and other processes to produce high-performance molybdenum products for various fields.
[0003] The main processes for the production of ammonium molybdate are: (1) Classic process: using high-soluble roasted molybdenum concentrate as raw material, and preparing ammonium molybdate through processes such as "acid washing-ammonia leaching-purification-acid precipitation"; (2) Water-washed acid-free process: using high-soluble roasted molybdenum concentrate as raw material, and preparing ammonium molybdate through processes such as "water washing-ammonia leaching purification-concentration crystallization"; (3) High-pressure oxygen leaching process: using molybdenum concentrate as raw material, and preparing ammonium molybdate through processes such as "high-pressure oxidation-ammonia leaching-purification-crystallization". The traditional ammonium molybdate production process has high requirements for the quality indicators of the raw material molybdenum concentrate. If the raw material quality indicators do not meet the standards, it may cause problems such as excessively high production costs and low molybdenum metal recovery rates.
[0004] The Chinese patent application document with application publication number CN1940096A discloses a process for wet recovery of low-grade molybdenum oxide concentrate, in which the molybdenum rough concentrate is mainly subjected to the steps of "grinding the molybdenum rough concentrate, adding sodium carbonate and sodium hydroxide reagents for leaching, solid-liquid separation, flotation of the leached residue to produce molybdenum concentrate, silicon removal by nitric acid, extraction of the filtered filtrate with a mixed solvent of N235, 2-octanol and kerosene, back extraction with ammonia water, and acid precipitation of the obtained ammonium molybdate solution" to obtain the ammonium molybdate product. In this process, the solubility of N235 in kerosene is low, and it is easy to precipitate to form a third phase. Although 2-octanol as a co-solvent can improve the phase separation effect, the presence of 2-octanol will increase the viscosity of the organic phase, resulting in a slow separation of the two phases; at the same time, 2-octanol is easy to reduce the interfacial tension between the aqueous phase and the organic phase, and it is easy to form an emulsion during the extraction process, resulting in difficulty in separating the aqueous phase and the organic phase. Summary of the invention
[0005] The existing production process of ammonium molybdate has problems such as separation difficulty. In order to solve this problem, the present invention provides a process for producing ammonium molybdate by an ion exchange method.
[0006] In order to achieve the purpose of the present invention, the present invention adopts the following technical solutions: The present invention provides a process for producing ammonium molybdate by an ion exchange method, comprising the following steps: S1: subjecting the molybdenum-containing ore to sodium roasting and water leaching to obtain a sodium molybdate solution; S2: adjusting the pH of the sodium molybdate solution and then adsorbing it with a modified anion exchange resin to obtain an adsorbed modified anion exchange resin and a post-exchange liquid; S3: desorbing the adsorbed modified anion exchange resin to obtain an ammonium molybdate solution; S4: After adjusting the pH of the ammonium molybdate solution, adding a precipitant to the ammonium molybdate solution, filtering, and obtaining a decontaminated ammonium molybdate solution; S5: Adsorbing the ammonium molybdate solution after impurities removal by cation exchange resin to obtain purified ammonium molybdate solution; S6: evaporating, concentrating and crystallizing the purified ammonium molybdate solution to obtain ammonium molybdate; In the step S1, the sodium-forming agent used in the sodium-forming roasting is sodium carbonate, and the mass ratio of the molybdenum-containing ore to the sodium carbonate is 1:1.25; the temperature of the sodium-forming roasting is 600-750°C, and the time of the sodium-forming roasting is 1-4h; the temperature of the water immersion is 75-90°C, and the time of the water immersion is 1.5-2h.
[0007] By adopting the above technical scheme, the molybdenum concentrate can be subjected to sodium roasting to convert molybdenum into compounds such as sodium molybdate, and the sulfur present in the molybdenum concentrate is transferred into sodium sulfate to reduce the generation of SO2; in the temperature range of 600-750°C, the molybdenum in the molybdenum concentrate can fully react with sodium carbonate and be completely converted, which is conducive to subsequent water leaching extraction; when the water leaching temperature is 75-90°C, the dissolution rate of soluble substances such as sodium molybdate in water can be accelerated.
[0008] Preferably, in step S2, the method for preparing the modified anion exchange resin comprises the following steps: (1) In an oxygen-free atmosphere, an anion exchange resin, benzyltrimethylammonium chloride and N,N-dimethylformamide are mixed evenly, ammonium persulfate is added, the temperature is raised to 35-45°C, the reaction is continued to be raised to 50-60°C, the reaction is continued for 10-15 hours, the mixture is filtered, washed and dried to obtain a quaternary ammonium modified anion exchange resin; (2) The quaternary ammonium modified anion exchange resin, 1-vinyl-3-butyl imidazole chloride and anhydrous ethanol are uniformly mixed, washed and dried to obtain a modified anion exchange resin.
[0009] Preferably, in step (1), the anion exchange resin is selected from one of D201 resin and D301 resin.
[0010] Preferably, in step (1), the ratio of anion exchange resin, benzyltrimethylammonium chloride and N,N-dimethylformamide is 1 g: (0.3-0.7) g: 80 mL.
[0011] By adopting the above technical scheme, at this ratio, the amount of benzyl vinyl trimethyl ammonium chloride is moderate, and it can be smoothly grafted to the resin surface under the initiation of ammonium persulfate, thereby improving the resin performance and the adsorption efficiency of molybdenum, while better maintaining the original pore structure of the resin.
[0012] Preferably, in step (1), the amount of ammonium persulfate used is 0.8%-1.2% of the total mass of the anion exchange resin and benzylvinyltrimethylammonium chloride.
[0013] By adopting the above technical solution, within the dosage range, the number of free radicals generated by the decomposition of ammonium persulfate can better meet the requirements of the grafting reaction, so that benzyl vinyl trimethyl ammonium chloride can be effectively grafted onto the resin surface, avoiding uneven distribution of the grafted chains.
[0014] The stepwise temperature increase reaction in step (1) can ensure the smooth progress of the grafting reaction, improve the grafting rate, and avoid excessive growth of the grafted chain and the occurrence of side reactions such as cross-linking.
[0015] Preferably, in step (2), the ratio of the quaternary ammonium modified anion exchange resin, 1-vinyl-3-butyl imidazolium chloride and anhydrous ethanol is 1 g: (0.1-0.3) g: 120 mL.
[0016] By adopting the above technical scheme, 1-vinyl-3-butylimidazolium chloride is impregnated into the resin surface, and positively charged 1-vinyl-3-butylimidazolium cations are introduced into the resin surface, thereby increasing the adsorption active sites of the resin for molybdate ions, and enhancing the electrostatic attraction between the resin surface and the molybdate ions; the 1-vinyl-3-butylimidazolium chloride impregnated on the resin surface can also complex with the molybdate ions, thereby improving the adsorption capacity for molybdate ions.
[0017] Preferably, in step (2), the mixing temperature is 25-35° C. and the mixing time is 20-26 h.
[0018] Preferably, in step S2, the pH is 6.5-8.
[0019] Preferably, in step S2, the liquid after delivery is sent to a reverse osmosis unit for concentration, and the concentrated liquid after reverse osmosis can be sent to a recovery device for recovering sodium salt, and the purified water separated by reverse osmosis is returned to the water immersion process for reuse.
[0020] By adopting the above technical solution, the sodium salt in the post-delivery liquid can be effectively enriched, and after further processing, it can be re-invested in the production process or used for other purposes, thereby reducing the amount of waste liquid discharged and realizing the recycling of resources.
[0021] Preferably, in step S4, the pH is 7-9; the precipitant is composed of polyaluminium chloride, polyacrylamide and magnesium sulfate in a mass ratio of (1-2): (0.01-0.05): (3-3.6).
[0022] By adopting the above technical scheme, the impurity removal effect is good when the pH is in the range of 7-9. When the pH exceeds this range, Mg(OH)2 precipitation is likely to occur, which consumes the amount of precipitant, reduces the precipitation rate of magnesium ammonium phosphate, magnesium silicate and magnesium arsenate, and deteriorates the impurity removal effect.
[0023] By adopting the above technical scheme, polyaluminium chloride can be hydrolyzed into aluminium hydroxide colloid in water, and impurities such as arsenic and phosphorus are adsorbed on the surface of the colloid; magnesium ions provided by magnesium sulfate react with arsenate, silicate, phosphate and the like to generate insoluble magnesium arsenate, magnesium silicate and magnesium phosphate precipitates, thereby reducing the concentration of arsenic, silicon and phosphorus ions in the solution; polyacrylamide further aggregates small particle flocs formed by polyaluminium chloride and magnesium sulfate, accelerates precipitation and separation, and the synergistic effect of the three improves the removal rate of impurity ions such as arsenic, silicon and phosphorus.
[0024] In summary, the beneficial effects of the present invention are: (1) The present invention grafts benzyltrimethylammonium chloride onto an anion exchange resin, introduces a positively charged quaternary ammonium salt group, provides more exchange sites for molybdate ions, and increases the adsorption of molybdate ions; 1-vinyl-3-butylimidazole chloride impregnated on the surface of the resin can complex with molybdate ions, and at the same time, it can further increase the adsorption of molybdate ions through electrostatic action; the synergistic effect of grafting and impregnation improves the adsorption efficiency of the modified anion exchange resin for molybdate ions; (2) The present invention uses a composite precipitant during impurity removal. Polyaluminium chloride is hydrolysed to adsorb arsenic, silicon and phosphorus ions, magnesium sulfate reacts with them to form a precipitate, and polyacrylamide is used to enhance flocculation. The synergistic effect of the three can significantly improve the removal rate of arsenic, silicon and phosphorus. (3) The present invention fully recovers molybdenum resources from molybdenum-containing ore through a sodium roasting-water leaching process, thereby greatly improving the recovery rate of molybdenum resources; the modified anion exchange resin is selected to achieve the separation, enrichment and conversion of low-concentration molybdenum resources; and the ammonium molybdate solution is decontaminated, thereby improving the quality of the ammonium molybdate product. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The present invention is a process flow chart for producing ammonium molybdate by the ion exchange method. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is explained in detail below with reference to several representative embodiments of the present invention.
[0027] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified.
[0028] The resins used in the following embodiments have all undergone a pretreatment process, specifically as follows: the resin is placed in a 5% sulfuric acid aqueous solution with a mass fraction of 3 times the resin volume, soaked for 12 hours, washed with water until neutral, then soaked in a 5% sodium hydroxide aqueous solution with a mass fraction of 3 times the resin volume for 12 hours, washed with water until neutral, and dried in a vacuum drying oven at 55°C for 10 hours for use.
[0029] The "post-exchange liquid" in the present invention refers to the liquid flowing out after the modified anion exchange resin completes the ion exchange process in step S2.
[0030] Example 1 The process of producing ammonium molybdate by an ion exchange method in this embodiment has the following specific steps: S1: 1 kg of molybdenum concentrate (Mo mass percentage is 33.74%) is mixed with 1.25 kg of sodium carbonate, crushed to 60 mesh, transferred to a muffle furnace, heated to 650 ° C and roasted for 3 hours; the molybdenum concentrate after roasting is crushed to 60 mesh, added to the leaching reactor, stirred, heated to 90 ° C, the water immersion time is 1.5 hours, filtered, the separated solid is transferred to the leaching reactor again for water immersion process, the water immersion is repeated 3 times, filtered, sodium molybdate solution is obtained, and the leached residue is recovered; S2: After adjusting the pH of the sodium molybdate solution to 6.5, a modified anion exchange resin was used for adsorption at 35°C to obtain the modified anion exchange resin and the post-exchange liquid after adsorption. The post-exchange liquid was sent to the reverse osmosis unit for concentration. The concentrated liquid after reverse osmosis was sent to the recovery equipment for recovering sodium salt. The purified water separated by reverse osmosis was returned to the water leaching process for reuse. The molybdenum adsorption rate was 98.74%; S3: After the modified anion exchange resin adsorbed in step S2 is rinsed with clean water, it is desorbed with a 10% by mass ammonia solution to obtain an ammonium molybdate solution; S4: After adjusting the pH of the ammonium molybdate solution to 8, add 2 g of polyaluminium chloride to the ammonium molybdate solution and stir for 30 min, add 6.5 g of magnesium sulfate and stir for 1 h, then add 0.04 g of polyacrylamide and stir for 30 min, filter, and obtain the ammonium molybdate solution after impurities are removed; S5: adjusting the pH of the ammonium molybdate solution after impurity removal to 7, and then adsorbing it with D112 resin at 30° C. to obtain a purified ammonium molybdate solution; S6: Evaporating, concentrating and crystallizing the purified ammonium molybdate liquid to obtain ammonium molybdate; the steam condensate generated during the evaporation and concentration process is returned to the water leaching process for reuse.
[0031] The process flow chart of producing ammonium molybdate by ion exchange is shown in Figure 1 .
[0032] The preparation method of the modified anion exchange resin of this embodiment comprises the following specific steps: (1) Under nitrogen atmosphere, 10 g of D201 resin, 4 g of benzyltrimethylammonium chloride and 80 mL of N,N-dimethylformamide were added to a four-necked flask and stirred for 20 min. 0.14 g of ammonium persulfate was added and the temperature was raised to 45 °C for reaction for 2 h. The temperature was further raised to 50 °C for reaction for 15 h. The mixture was filtered and extracted with acetone for 24 h. The mixture was dried in a vacuum oven at 60 °C for 10 h to obtain a quaternary ammonium modified anion exchange resin. (2) Add 10 g of quaternary ammonium modified anion exchange resin, 1.5 g of 1-vinyl-3-butyl imidazole chloride and 120 mL of anhydrous ethanol into a flask and stir for 15 min. Oscillate in a water bath constant temperature oscillator at 25 °C for 24 h, wash, and dry in a vacuum drying oven at 40 °C for 12 h to obtain a modified anion exchange resin.
[0033] Example 2 The process of producing ammonium molybdate by an ion exchange method of this embodiment has the following specific steps: S1: 1 kg of molybdenum concentrate (the mass percentage of Mo is 33.74%) is mixed with 1.25 kg of sodium carbonate, crushed to 60 mesh, transferred to a muffle furnace, heated to 750°C and roasted for 2 hours; the molybdenum concentrate after roasting is crushed to 60 mesh, added to a leaching reactor, stirred, heated to 75°C, and the water immersion time is 2 hours, filtered, and the separated solid is transferred to the leaching reactor again for water immersion process, and the water immersion is repeated 3 times, filtered, and sodium molybdate solution is obtained, and the leached residue is recovered; S2: After adjusting the pH of the sodium molybdate solution to 7, a modified anion exchange resin was used for adsorption at 35°C to obtain the modified anion exchange resin and the exchange liquid after adsorption. The exchange liquid was sent to the reverse osmosis unit for concentration. The concentrated liquid after reverse osmosis was sent to the recovery equipment for recovering sodium salt. The purified water separated by reverse osmosis was returned to the water leaching process for reuse. The molybdenum adsorption rate was 98.22%; S3: After the modified anion exchange resin adsorbed in step S2 is rinsed with clean water, it is desorbed with a 10% by mass ammonia solution to obtain an ammonium molybdate solution; S4: After adjusting the pH of the ammonium molybdate solution to 7, add 2 g of polyaluminium chloride to the ammonium molybdate solution and stir for 30 min, add 7.2 g of magnesium sulfate and stir for 1 h, then add 0.02 g of polyacrylamide and stir for 30 min, filter, and obtain the ammonium molybdate solution after impurities are removed; S5: adjusting the pH of the ammonium molybdate solution after impurity removal to 7, and then adsorbing it with D112 resin at 30° C. to obtain a purified ammonium molybdate solution; S6: Evaporating, concentrating and crystallizing the purified ammonium molybdate liquid to obtain ammonium molybdate; the steam condensate generated during the evaporation and concentration process is returned to the water leaching process for reuse.
[0034] The preparation method of the modified anion exchange resin of this embodiment comprises the following specific steps: (1) Under nitrogen atmosphere, 10 g of D201 resin, 7 g of benzylvinyltrimethylammonium chloride and 80 mL of N,N-dimethylformamide were added to a four-necked flask and stirred for 20 min. 0.14 g of ammonium persulfate was added and the temperature was raised to 40 °C for reaction for 3 h. The temperature was further raised to 60 °C for reaction for 10 h. The mixture was filtered and extracted with acetone for 24 h. The mixture was dried in a vacuum oven at 60 °C for 10 h to obtain a quaternary ammonium modified anion exchange resin. (2) Add 10 g of quaternary ammonium modified anion exchange resin, 2 g of 1-vinyl-3-butylimidazole chloride and 120 mL of anhydrous ethanol into a flask and stir for 15 min. Oscillate in a water bath constant temperature oscillator at 30 °C for 20 h, wash, and dry in a vacuum drying oven at 40 °C for 12 h to obtain a modified anion exchange resin.
[0035] Example 3 The process of producing ammonium molybdate by an ion exchange method of this embodiment has the following specific steps: S1: 1kg of molybdenum concentrate (the mass percentage of Mo is 56.52%) is mixed with 1.25kg of sodium carbonate, crushed to 60 mesh, transferred to a muffle furnace, heated to 700℃ and roasted for 1h; the molybdenum concentrate after roasting is crushed to 60 mesh, added to the leaching reactor, stirred, heated to 80℃, and the water immersion time is 2h, filtered, and the separated solid is transferred to the leaching reactor again for water immersion process, and the water immersion is repeated 3 times, filtered, and sodium molybdate solution is obtained, and the leached residue is recovered; S2: After adjusting the pH of the sodium molybdate solution to 8, a modified anion exchange resin is used for adsorption at 35°C to obtain the modified anion exchange resin and the exchange liquid after adsorption. The exchange liquid is sent to the reverse osmosis unit for concentration. The concentrated liquid after reverse osmosis is sent to the recovery equipment for recovering sodium salt. The purified water separated by reverse osmosis is returned to the water leaching process for reuse. The molybdenum adsorption rate is 99.52%; S3: After the modified anion exchange resin adsorbed in step S2 is rinsed with clean water, it is desorbed with a 10% by mass ammonia solution to obtain an ammonium molybdate solution; S4: After adjusting the pH of the ammonium molybdate solution to 9, 3 g of polyaluminium chloride was added to the ammonium molybdate solution and stirred for 30 min, 6 g of magnesium sulfate was added and stirred for 1 h, and then 0.08 g of polyacrylamide was added and stirred for 30 min, and filtered to obtain the ammonium molybdate solution after impurities were removed; S5: adjusting the pH of the ammonium molybdate solution after impurity removal to 7, and then adsorbing it with D112 resin at 30° C. to obtain a purified ammonium molybdate solution; S6: Evaporating, concentrating and crystallizing the purified ammonium molybdate liquid to obtain ammonium molybdate; the steam condensate generated during the evaporation and concentration process is returned to the water leaching process for reuse.
[0036] The preparation method of the modified anion exchange resin of this embodiment comprises the following specific steps: (1) Under nitrogen atmosphere, 10 g of D301 resin, 6 g of benzyltrimethylammonium chloride and 80 mL of N,N-dimethylformamide were added to a four-necked flask and stirred for 20 min. 0.19 g of ammonium persulfate was added and the temperature was raised to 35 °C for reaction for 1 h. The temperature was further raised to 55 °C for reaction for 12 h. The mixture was filtered and extracted with acetone for 24 h. The mixture was dried in a vacuum oven at 60 °C for 10 h to obtain a quaternary ammonium modified anion exchange resin. (2) Add 10 g of quaternary ammonium modified anion exchange resin, 3 g of 1-vinyl-3-butylimidazole chloride and 120 mL of anhydrous ethanol into a flask and stir for 15 min. Oscillate in a water bath constant temperature oscillator at 35 °C for 26 h, wash, and dry in a vacuum drying oven at 40 °C for 12 h to obtain a modified anion exchange resin.
[0037] Example 4 The process of producing ammonium molybdate by an ion exchange method of this embodiment has the following specific steps: S1: 1kg of molybdenum concentrate (the mass percentage of Mo is 56.52%) is mixed with 1.25kg of sodium carbonate, crushed to 60 mesh, transferred to a muffle furnace, heated to 600℃ and roasted for 4h; the molybdenum concentrate after roasting is crushed to 60 mesh, added to the leaching reactor, stirred, heated to 85℃, and the water immersion time is 1.5h, filtered, and the separated solid is transferred to the leaching reactor again for water immersion process, and the water immersion is repeated 3 times, filtered, and sodium molybdate solution is obtained, and the leached residue is recovered; S2: After adjusting the pH of the sodium molybdate solution to 7.5, a modified anion exchange resin is used for adsorption at 35°C to obtain the modified anion exchange resin and the exchange liquid after adsorption. The exchange liquid is sent to the reverse osmosis unit for concentration. The concentrated liquid after reverse osmosis is sent to the recovery equipment for recovering sodium salt. The purified water separated by reverse osmosis is returned to the water leaching process for reuse. The molybdenum adsorption rate is 99.15%; S3: After the modified anion exchange resin adsorbed in step S2 is rinsed with clean water, it is desorbed with a 10% by mass ammonia solution to obtain an ammonium molybdate solution; S4: After adjusting the pH of the ammonium molybdate solution to 9, 2 g of polyaluminium chloride was added to the ammonium molybdate solution and stirred for 30 min, 6.5 g of magnesium sulfate was added and stirred for 1 h, and then 0.04 g of polyacrylamide was added and stirred for 30 min, and filtered to obtain the ammonium molybdate solution after impurities were removed; S5: adjusting the pH of the ammonium molybdate solution after impurity removal to 7, and then adsorbing it with D112 resin at 30° C. to obtain a purified ammonium molybdate solution; S6: Evaporating, concentrating and crystallizing the purified ammonium molybdate liquid to obtain ammonium molybdate; the steam condensate generated during the evaporation and concentration process is returned to the water leaching process for reuse.
[0038] The preparation method of the modified anion exchange resin of this embodiment comprises the following specific steps: (1) Under nitrogen atmosphere, 10 g of D201 resin, 3 g of benzyltrimethylammonium chloride and 80 mL of N,N-dimethylformamide were added to a four-necked flask and stirred for 20 min. 0.13 g of ammonium persulfate was added and the temperature was raised to 30 °C for reaction for 2 h. The temperature was further raised to 50 °C for reaction for 15 h. The mixture was filtered and extracted with acetone for 24 h. The mixture was dried in a vacuum oven at 60 °C for 10 h to obtain a quaternary ammonium modified anion exchange resin. (2) Add 10 g of quaternary ammonium modified anion exchange resin, 1 g of 1-vinyl-3-butyl imidazole chloride and 120 mL of anhydrous ethanol into a flask and stir for 15 min. Oscillate in a water bath constant temperature oscillator at 25 °C for 22 h, wash, and dry in a vacuum drying oven at 40 °C for 12 h to obtain a modified anion exchange resin.
[0039] The ammonium molybdate products prepared in Examples 1 to 4 of the present invention all meet the testing standards of GB / T 3460-2017 Ammonium Molybdate.
[0040] Comparative Example 1 The difference from Example 1 is that the preparation of the modified anion exchange resin in this comparative example does not involve the preparation of step (2), and the rest is the same as Example 1; The molybdenum adsorption rate in this comparative example is 94.34%; the resin is not impregnated, so that the sites of molybdate ions adsorbed on the resin surface are reduced; at the same time, the substances complexed with molybdate ions on the resin surface are reduced, and therefore, the adsorption rate of molybdenum by the resin is reduced.
[0041] Comparative Example 2 The difference from Example 1 is that the preparation of the modified anion exchange resin in this comparative example does not involve the preparation of step (1), and the rest is the same as Example 1; The molybdenum adsorption rate in this comparative example is 92.52%; benzyl vinyl trimethyl ammonium chloride is introduced into the resin, and the quaternary ammonium cations present in its molecules can form electrostatic attraction with molybdate ions. Compared with the case where no ammonium chloride is introduced, the number of sites where the resin can adsorb molybdate ions increases, thereby effectively improving the adsorption rate of the resin for molybdate ions.
[0042] Comparative Example 3 The difference from Example 1 is that in step S2 of this comparative example, D201 resin is used instead of modified anion exchange resin, and the rest is the same as Example 1; The molybdenum adsorption rate in this comparative example is 90.02%. Compared with the unmodified D201 resin, the modified D201 resin increases the adsorption sites for molybdate ions, and there is a complexation effect on the molybdate ions on the resin surface. Therefore, the adsorption rate of molybdenum by the modified D201 resin is stronger than that of the D201 resin.
[0043] Comparative Example 4-Comparative Example 6 The difference from Example 1 is that the amount of the precipitant in step S4 is changed in this comparative example, as shown in Table 1, and the removal rates of arsenic, silicon and phosphorus are shown in Table 2. The rest are the same as Example 1.
[0044] Table 1 Dosage of precipitant
[0045] Table 2 Removal rate results
[0046] It can be seen from Table 1 and Table 2 that the components and dosage ratio of polyaluminium chloride, magnesium sulfate and polyacrylamide in the precipitant have been optimized. Any change in the components and dosage ratio will affect the removal rate of arsenic, silicon and phosphorus impurities.
[0047] The above is an exemplary description of the present invention. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or equivalent replacement that can be done by other technicians in this field without expending creative labor falls within the protection scope of the present invention.
Claims
1. A process for producing ammonium molybdate by ion exchange, characterized in that: The steps include: S1: subjecting the molybdenum-containing ore to sodium roasting and water leaching to obtain a sodium molybdate solution; S2: adjusting the pH of the sodium molybdate solution and then adsorbing it with a modified anion exchange resin to obtain an adsorbed modified anion exchange resin and a post-exchange liquid; S3: desorbing the adsorbed modified anion exchange resin to obtain an ammonium molybdate solution; S4: After adjusting the pH of the ammonium molybdate solution, adding a precipitant to the ammonium molybdate solution, filtering, and obtaining a decontaminated ammonium molybdate solution; S5: Adsorbing the ammonium molybdate solution after impurities removal by cation exchange resin to obtain purified ammonium molybdate solution; S6: evaporating, concentrating and crystallizing the purified ammonium molybdate solution to obtain ammonium molybdate; In the step S1, the sodium-forming agent used in the sodium-forming roasting is sodium carbonate, and the mass ratio of the molybdenum-containing ore to the sodium carbonate is 1:1.25; the temperature of the sodium-forming roasting is 600-750° C., and the time of the sodium-forming roasting is 1-4 hours.
2. The process for producing ammonium molybdate by an ion exchange method according to claim 1, characterized in that: In step S1, the water immersion temperature is 75-90° C., and the water immersion time is 1.5-2 hours.
3. The process for producing ammonium molybdate by an ion exchange method according to claim 1, characterized in that: In step S2, the preparation method of the modified anion exchange resin comprises the following steps: (1) In an oxygen-free atmosphere, an anion exchange resin, benzyltrimethylammonium chloride and N,N-dimethylformamide are mixed evenly, ammonium persulfate is added, the temperature is raised to 35-45°C, the reaction is continued to be raised to 50-60°C, the reaction is continued for 10-15 hours, the mixture is filtered, washed and dried to obtain a quaternary ammonium modified anion exchange resin; (2) The quaternary ammonium modified anion exchange resin, 1-vinyl-3-butyl imidazole chloride and anhydrous ethanol are uniformly mixed, washed and dried to obtain a modified anion exchange resin.
4. The process for producing ammonium molybdate by an ion exchange method according to claim 3, characterized in that: In the step (1), the usage ratio of anion exchange resin, benzyltrimethylammonium chloride and N,N-dimethylformamide is 1 g: (0.3-0.7) g: 80 mL.
5. The process for producing ammonium molybdate by an ion exchange method according to claim 3, characterized in that: In the step (1), the amount of ammonium persulfate used is 0.8%-1.2% of the total mass of the anion exchange resin and benzyltrimethylammonium chloride.
6. The process for producing ammonium molybdate by an ion exchange method according to claim 3, characterized in that: In the step (2), the ratio of the quaternary ammonium modified anion exchange resin, 1-vinyl-3-butyl imidazole chloride and anhydrous ethanol is 1 g: (0.1-0.3) g: 120 mL.
7. The process for producing ammonium molybdate by an ion exchange method according to claim 3, characterized in that: In the step (2), the mixing time is 20-26 hours.
8. The process for producing ammonium molybdate by ion exchange according to claim 1, characterized in that: In step S2, the pH is 6.5-8.
9. The process for producing ammonium molybdate by ion exchange according to claim 1, characterized in that: In the step S4, the pH is 7-9; the precipitant is composed of polyaluminium chloride, polyacrylamide and magnesium sulfate in a mass ratio of (1-2): (0.01-0.05): (3-3.6).
Citation Information
Patent Citations
Extraction of vanadium and molybdenum compound from refused materials containing vanadium and molybdenum etc. multiple elements
CN1940096A
Photosensitive dipping resin
CN102093809A
Resourceful utilization method of waste catalyst
CN104628035A
Gel type imidazolyl anion exchange resin as well as preparation method and application thereof
CN119463003A
Method for separating rhenium from rhenium-containing solution by adopting anion exchange resin
CN119464782A